2004
DOI: 10.1177/0739986303262604
|View full text |Cite
|
Sign up to set email alerts
|

Entering and Succeeding in the “Culture of College”: The Story of Two Mexican Heritage Students

Abstract: In this retrospective study, the academic resilience of two individuals of Mexican heritage who graduated from Stanford University is described. The respondents (a woman and a man) now in their early 20s came from home backgrounds of extreme impoverishment and adversity. By means of in-depth interviews the challenges the two respondents faced in school beginning in kindergarten and continuing through their graduation from Stanford is described. Both respondents attribute their academic success to the support g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
91
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 13 publications
9
91
0
2
Order By: Relevance
“…Exercise and physical activity are associated with increased positive aspects that are conditioned to respond and provide opportunities to reduce the negative impacts of threatening situations and antigenics (10). By creating an appropriate context to increase their sense of empowerment and self-worth (11), athletic people are able to reduce psychological, emotional and affective (e.g., alexithymia and its components) problems more so than nonathletic people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise and physical activity are associated with increased positive aspects that are conditioned to respond and provide opportunities to reduce the negative impacts of threatening situations and antigenics (10). By creating an appropriate context to increase their sense of empowerment and self-worth (11), athletic people are able to reduce psychological, emotional and affective (e.g., alexithymia and its components) problems more so than nonathletic people.…”
Section: Discussionmentioning
confidence: 99%
“…Strohle (1996) showed that exercise and physical activity can reduce depression and anxiety (9). In Cabrera and Padilla's research (2004), it was shown that student athletes have relatively high emotional intelligence, which has a positive impact on their athletic performance (10). Cox (2002) stated that athletes have lower negative emotional states and higher vitality in comparison with nonathletes (11).…”
Section: Introductionmentioning
confidence: 99%
“…Mucho más escasos son los estudios que se centran en la vida de los escolares a través de relatos realizados en tiempo presente (Cabrera & Padilla, 2004). Destacamos el trabajo de Nallely Garza (2013) sobre las narrativas de estudiantes de educación secundaria en México con diarios temáticos para lograr un mayor conocimiento de cómo los jóvenes manifiestan y describen su experiencia en esa etapa de formación.…”
Section: Introductionunclassified
“…These characteristics of resilient students are vital as it is believed that these factors can influence effective teaching and learning. Therefore, it is suggested that schools, parents, communities, and peers should promote these protective factors by providing supportive environments and opportunities to promote life skills and to take part in social life (Arastaman & Balci, 2013;Cabrera & Padilla, 2004;Dass-Brailsford 2005;Thornton, Collins & Daugherty, 2006;Pisapia & Westfall, 1994).…”
Section: Introductionmentioning
confidence: 99%